2021
DOI: 10.1111/vsu.13591
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of canine chondrocytes and synoviocytes to antibiotic cytotoxicity in vitro

Abstract: Objective: To evaluate relative cytotoxicity of antibiotics to normal canine joint tissues in vitro. Study design: Experimental in vitro study. Sample population: Chondrocytes and synoviocytes (three dogs); cartilage explants (three dogs); six dogs total. Methods: Chondrocytes and synoviocytes from normal femoropatellar joints of three dogs were plated on 24-well plates (50 000 cells/cm 2 , triplicate, 48 hours) and exposed to antibiotics (ampicillin sulbactam, vancomycin, cefazolin, ceftazidime, amikacin, enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The cytotoxicity of concentrated vancomycin (up to 50 mg/mL) was demonstrated in an in vitro study over 48 h [12]. Other studies have also demonstrated the cytotoxicity of various antibiotics against articular cartilage and other relevant cells [12][13][14][15]. Studies show that cytotoxicity is concentration-dependent [13][14][15].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The cytotoxicity of concentrated vancomycin (up to 50 mg/mL) was demonstrated in an in vitro study over 48 h [12]. Other studies have also demonstrated the cytotoxicity of various antibiotics against articular cartilage and other relevant cells [12][13][14][15]. Studies show that cytotoxicity is concentration-dependent [13][14][15].…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have also demonstrated the cytotoxicity of various antibiotics against articular cartilage and other relevant cells [12][13][14][15]. Studies show that cytotoxicity is concentration-dependent [13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…Histopathological analyses have confirmed that this antibiotic causes a decrease in matrix proteoglycans, total cartilage thickness, a decrease in the number of chondrocytes, the appearance of spindle cells, and an increase in the number of gaps and voids in the articular cartilage matrix in young lambs [ 113 ]. Moreover, safety studies of enrofloxacin confirmed that the use of this antibiotic causes a drastic decrease in the viability of chondrocytes, induces their apoptosis and DNA fragmentation, causes an increase in pro-inflammatory factors, such as Il-1β, TNF, and MMP3, and can affect the shape of the actin and vimentin cytoskeleton [ 114 , 115 , 116 , 117 ]. Analogous results were obtained in safety studies of enrofloxacin in growing hens.…”
Section: The Safety Of Enrofloxacin Usementioning
confidence: 99%
“…39 While studies have shown that higher concentrations of certain antibiotics are increasingly cytotoxic to certain chondrocyte cell lines in vitro, methods for preserving a noninfectious graft are required, and further evaluation of effects of antibiotics on chondrocyte viability is warranted to optimize osteochondral allograft storage. 43,44…”
Section: Antibioticsmentioning
confidence: 99%